Kajian Yuridis Terhadap Perjanjian Utang Piutang Tidak Tertulis - Muhammad Fikri Ramadhan; Kairuddin Karim; Auliah Ambarwati (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This study aims to determine the legal basis that can bind unwritten debt agreements and to determine the strength of unwritten debt agreements as evidence. This study uses a type of normative legal research with a statutory approach and an analytical approach by examining and analyzing the legal issues being faced. The results of the research show that the legal basis that binds an unwritten debt agreement is contained in article 1313 of the Civil Code which states that an agreement is an act by which one or more parties bind themselves to another or more people. So the unwritten debt agreement must comply with the legal requirements of an agreement by Article 1320 of the Civil Code. And legally valid agreements apply as laws for those who make them, this is by Article 1338 Paragraph (1). For evidence that can be used in the event of a default on one of the parties, that is, you can use evidence of testimony (by bringing in more than one witness) and can be strengthened by electronic mail evidence.